Mini Review: Potential of Scrap Tires for Useful Material and Products - Muhammad Latifur Rochman; Muji Setiyo (Jurnal Teknik Mesin, 2019)
One of the effects of increasing the number of vehicles is the presence of scrap tires. Stacking and burial of scrap tires have caused serious problems for the environment. Therefore, this article presents a brief review of the potential of scrap tires to be useful materials and products. Of the many potential uses, we find at least three ways to use the scrap tires, which are: converted to rubber powder to be reprocessed as asphalt mixture, concrete mixtures, composite mixes, fillers, and the like; converted to liquid oil through the pyrolysis process; and recycled forms, where the original physical properties of used tires are still visible, such as for furniture, wave breakers, racing circuit safety, and the like.